On the Operating Efficiency of the Commercial Banking Sector in Malaysia : Empirical Evidence (Malaysian Management Journal, 1995)
It has been argued and recognised in the literature on economic development that finance is inevitable for economic growth. The ability of financial institutions to perform their basic role as an intermediary between savers and investors in the financial system affects the performance of the economy as a whole. Thus, it is not surprising that the efficiency of the financial markets, particularly the banking sector, must by now be one of the most intensively researched topics in economics, especially in developed countries such as the United States, Canada and the United Kingdom. The purpose of this study is to complement the literature on banking efficiency, with respect to a developing country, namely, Malaysia. In this study, we used three approaches â€” single-output bank cost function, multiproduct bank cost function and profitability analysis â€” to identify whether the banking sector in Malaysia exhibits scale economies. The study used cross-sectional data for the 1984-1986 period. Results of our multiproduct bank cost function approach show that, as a whole, the banking sector in Malaysia exhibits decreasing ray average cost or economies of scale. Further, our results indicate that banks exhibit economies of scope or interproduct complementarity among various outputs. However, it was also revealed that foreign banks in Malaysia do not experience scale economies. This is probably due to the fact that current regulations do not permit foreign banks to establish their branches in the country. As such, the banks do not have the opportunity to spread their operating costs more 'evenly' compared to domestic banks.